Effect of inhaled procaterol and budesonide on right ventricular diastolic function in children with asthma - Alit Utamayasa; Najib Advani; Imam Boediman; Sudigdo Sastroasmoro; Bambang Madiyono (Paediatrica Indonesiana, 2009)
Objectives To study changes in parameters of right ventricular(RV) diastolic function after procaterol and budesonide inhalationin children with asthma.Methods This was a one-group pretest-posttest design to determinechanges in right ventricular diastolic function followingfour weeks of inhaled procaterol and budesonide administration.Subjects were children aged 8 to 18 years with frequent episodicasthma recruited consecutively at the Department of ChildHealth, Cipto Mangunkusumo Hospital. M-mode and 2-Dechocardiography examinations were performed to determine RVisovolumetric relaxation time (IVRT), acceleration time (AT),deceleration time (DT), E wave, A wave, E/ A ratio, and tricuspidannular plane systolic excursion (TAPSE). Means of the RVfunction parameters before and after treatment were comparedusing the paired t-test or Wilcoxon test.Results There were 29 patients comprising 16 boys and 13 girls. Themeans or medians of theE wave, A wave, E/A ratio, accelerationtime (AT), deceleration time (DT), and isovolumetric relaxationtime (IVRT) before and after treatment were 0.55 and 0.55 em/sec(P=0.709), 0.45 and 0.35 em/sec (P<O.OOOl), 1.17 and 1.58 em/sec(P<0.0001), 52.73 and 55.03 m/sec (P=0.04), 55.39 and 58.10 m/sec (P=0.03), and 46.50 and 70.0 m/sec (P<0.0001), respectively.The median pre- and post-inhalation TAPSE were 1.63 and 1.84em, respectively (P<0.001).Conclusions In children with frequent episodic asthma, thereare changes in RV diastolic functions IVRT, AT, DT, E/A ratioand A wave following procaterol and budesonide inhalation.There was no increase in E wave following inhalation. TAPSEwas increased following procaterol and budesonide inhalation.